Clinical and Psychological Variables Present in Patients with Chronic Back Pain - Ahmed José Pomares Avalos; Teresa Rodríguez Rodríguez; José Antonio Pomares Alfonso (Revista Finlay)
Background: chronic back pain is regarded as a major public health problem with a substantial socio-economic impact. Objective: to determine the main clinical and psychological variables present in patients with chronic back pain. Methods: a case series study including the comparison of variables was conducted from July to December 2015 at the Dr. Gustavo Aldereguía Lima Hospital in Cienfuegos. The study variables were: age, sex, educational level, occupation, origin, characteristics of pain (intensity, frequency, duration, type of treatment used for its relief), anxiety, depression, anger and hostility as personality traits, and anxiety, depression and stress as negative emotional states. A non-probability sample of patients with chronic back pain was used. The information was obtained through a questionnaire and various psychological instruments. Results: predominant psychological variables were pathological stress as negative emotional state, as well as trait anxiety and depression. The prevailing clinical variables were moderate intensity of pain, episodic occurrence, duration longer than 2 years and medical treatment as the most frequent type of treatment used. Conclusions: high trait anxiety and pathological stress as negative emotional state coexist in patients with chronic back pain. These psychological aspects may be influencing the presence and clinical characteristics of pain.